STUDI AWAL IMPLEMENTASI E-LEARNING DI MATA KULIAH ALGORITMA DAN PEMROGRAMAN 2 SEBAGAI ALAT BANTU MEDIA PEMBELAJARAN - Dwi Budi Srisulistiowati; Asep Ramdhani Mahbub (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2020)
E-learning as a learning media in education that provides a very important role and a great function for the education world which has been charged with many shortcomings and weaknesses of education such as the limitations of space and time in the teaching and learning process emphasizing the efficiency of learning in order to get full teaching even though not must be face to face can also be accessed anywhere, anytime, in accordance with the assignments given by instructors are usually scheduled with a specified deadline. The philosophy of the University of Bhayangkara Jakarta Raya in carrying out its function as a manager and organizer of higher education is essentially carrying out the function of public services. The motto of the University of Bhayangkara Jakarta Raya is: "Service that never knows the end for the development of the University of Bhayangkara Jakarta Raya in an effort to participate in educating and prospering the lives of the people, nation and state". The problem that arises is the limitations in the face-to-face traditional teaching process. Then comes e-learning as an alternative technology in learning. This research includes implementation research, which aims to produce e-learning media on the Algorithm and Programming 2 subject. The subject of this research is the second semester Inforrmatic Engineering students. The application used is Moodle.Â Keywords: E-Learning, Moodle, Learning Media.